Koncepce bytové politiky v ČR - Paclíková, Aneta (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Tématem této bakalářské práce je Koncepce bytové politiky v ČR. Práce je rozdělena na čtyři hlavní části. První část se zabývá obecnou charakteristikou bytové politiky, popisuje roli státu a její cíle. Poté je popsána státní bytová koncepce z roku 2011. Druhá část představuje dostupné podpory bydlení. Třetí část se zabývá vývojem bytové výstavby v ČR a poslední část je zaměřena na bytovou politiku města Litomyšl.

The topic of the bachelor’s thesis is Conception of the Housing Policy in the CR. It is divided into four main parts. The first part explains general characteristics of the housing policy, describes the role of the state and her goals. Then is presented the state housing concept from 2011. The second part introduces available support housing. The third part explains proceses housing construction in the CR and last part is focused on the housing policy of town Litomyšl.
Conception of the Housing Policy in the CR
Keywords: Bydlení; bytová politika; bytová výstavba; státní bytová koncepce; nástroje bytové politiky; bytový fond; správa bytového fondu; dotační programy; Litomyšl.; Housing; housing policy; housing construction; state housing conception; tools of the housing policy; housing fun; management of the housing fund; subsidy programs; Litomyšl.